2016
DOI: 10.1590/s0100-204x2016000600012
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade de ingredientes em dietas para juvenis de pacamã (Lophiosilurus alexandri)

Abstract: Resumo -O objetivo deste trabalho foi determinar o coeficiente de digestibilidade aparente (CDA) de seis ingredientes, em dietas-referência prática e purificada, e determinar a influência das dietas-referência sobre a digestibilidade dos ingredientes em juvenis de pacamã. Avaliaram-se os seguintes ingredientes: farinha de peixe, farinha de carne e ossos, farelo de soja, soja integral tostada, farelo de trigo e protenose de milho. Houve interação entre a dieta-referência e os ingredientes estudados. A dieta pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Studies have reported the occurrence of nutrient leaching in digestibility assays due to long intervals between faecal collections (Abimorad & Abimorad & Carneiro, 2004; Kitagima & Fracalossi, 2010). In the present study, faeces were collected immediately after defecation, whereas in the study by Teixeira et al (2010), faeces were collected after 1 h. In the study by Melo et al (2016), this interval was not reported. We suggest that the short time between faecal collections in this study prevented faecal nutrient leaching, improving the reliability of our results.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Studies have reported the occurrence of nutrient leaching in digestibility assays due to long intervals between faecal collections (Abimorad & Abimorad & Carneiro, 2004; Kitagima & Fracalossi, 2010). In the present study, faeces were collected immediately after defecation, whereas in the study by Teixeira et al (2010), faeces were collected after 1 h. In the study by Melo et al (2016), this interval was not reported. We suggest that the short time between faecal collections in this study prevented faecal nutrient leaching, improving the reliability of our results.…”
Section: Discussioncontrasting
confidence: 51%
“…The ADC of wheat bran crude protein for pirarucu was lower than that for the freshwater carnivore pacamã ( Lophiosilurus alexandri , 83.50%) (Melo et al, 2016). The ACDs for corn, broken rice and sorghum were also lower than that for surubim (87.40%, 85.30% and 81.11% respectively) (Teixeira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not evaluated digestibility, we believe that the increase in these biochemical variables may be related to the beneficial effect of OEO on the digestion of nutrients, including lipids and carbohydrates, the latter with reduced digestibility in carnivorous fish such as L . alexandri (Melo et al, 2016). In addition, the increase in cholesterol levels probably did not lead to a greater deposition of lipids, since there were no changes in carcass lipid content and viscerosomatic, hepatosomatic and visceral fat indices.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies has been conducted with the aim of expanding knowledge regarding reproduction, physiology and growth of the species (Costa et al, 2015; Silva et al, 2019; Takata et al, 2018). Moreover, the species has potential for aquaculture because of the quality of its flesh (Sant'ana et al, 2014) and its ability to be conditioned to accept formulated diets via different methods of feed‐conditioning (Cordeiro et al, 2016; Luz et al, 2011), which has facilitated studies of nutrition and large scale production for the species (Melo et al, 2016; Santos et al, 2012). However, there is no information about the effects of salinity on muscle development and gill tissue for L. alexandri juvenile.…”
Section: Introductionmentioning
confidence: 99%